1999
DOI: 10.1088/0022-3727/32/19/301
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the potential of polarized light scattering for the characterization of irregular particles

Abstract: An investigation has been carried out into the possibility of using polarization methods to characterize clouds of irregular particles. Measurements were made at scattering angles between approximately 115 • and 135 • , where it was expected that polarization effects would have maximum variation with shape. It was found that the angular variation of any polarization property was similar for most particles. Further, as a consequence of reciprocity, the useful parameters were limited to the scattered intensities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…For uniform sphere particles, equals 1 in the backward direction [27]. It was also shown that the ratio of to highly correlates with the average roundness of particles [39].…”
Section: Alterations Of Tissue Microarchitectures In Early Carcinomentioning
confidence: 91%
“…For uniform sphere particles, equals 1 in the backward direction [27]. It was also shown that the ratio of to highly correlates with the average roundness of particles [39].…”
Section: Alterations Of Tissue Microarchitectures In Early Carcinomentioning
confidence: 91%
“…Within these considerations, the particles can have any size, shape, orientation and distribution; but we will assume further that the medium is isotropic, an isotropy that may be only in the statistical sense. This class of scattering media have been studied extensively and several applications have been discussed [13,14,15,16,17,18]. Fig.…”
Section: Depolarization Properties Of An Ensemble Of Randomly Orientementioning
confidence: 99%
“…A value greater than unity for these parameters is termed "anomalous depolarization" [21]. As a matter of fact, many experimental and theoretical results up to date show that for disordered media the cross-polarization ratios are never simultaneously greater than unity [14,15,16,17]. We proceed our simulation by randomly choosing the free parameters m 01 , m 11 , m 22 , m 23 and m 33 in the range −1 ≤ m i j ≤ 1.…”
Section: Depolarization Properties Of An Ensemble Of Randomly Orientementioning
confidence: 99%
“…Remind that q = 1 for identical spheres. We see, therefore, that backscattering region is potentially informative for the different particulate media discrimination (Card and Jones 1999).…”
Section: The Normalized Phase Matrixmentioning
confidence: 73%
“…So there will be no light coming from the system of spherical particles, placed between crossed polarizers. This is not the case for irregularly shaped particles (Card and Jones 1999). Note, that both q and r do not depend on the size of particles in the framework of the geometrical optics approximation (Kokhanovsky and Jones 2002).…”
mentioning
confidence: 90%